Perceptions of Alumni Customer Service Experiences as a Factor of Alumni Giving at Three Historically Black Universities in the Southeastern United States - Barnes, Marc A.; Okojie, Felix A. (Advances in Social Sciences Research Journal, 2023)
The purpose of this study was to gain an in-depth understanding of universities’ alumni perceptions of customer service experiences as a factor of Alumni giving at Historically Black Colleges and Universities (HBCUs) in the Southeast. Research shows that the overall undergraduate experience, the quality of academic instruction, and students’ engagement on campus impact donor giving decisions. The quality of customer service as an additional factor of alumni giving was the subject of this study. Guided by Oliver’s (1980) expectancy disconfirmation framework, this phenomenological study utilized one-on-one interviews of alumni from three HBCUs in the Southeastern United States to determine if the perceptions of their customer service experience as undergraduate students impacted their decisions to make a financial contribution to their alma mater. The findings of the study show that alumni perceptions of the service received impacted their willingness and non-willingness to become donors.